Teletherapy could miss a distinct group among patients with pain and opioid use disorder - Sarah C. Wilson; Alexandra M. Otto; Amy B. Wachholtz (Discover Psychology)
Abstract The COVID-19 pandemic highlighted a pre-existing issue related to healthcare accessibility, especially for comorbid chronic pain and opioid use disorder (OUD) populations. Though researchers and practitioners have relied on telehealth to address barriers to healthcare, telehealth services remain inaccessible for many. This study explored the effectiveness of strategies used to continue a clinical trial for comorbid chronic pain and OUD during the COVID-19 pandemic. This study involved the transition of in-person group psychotherapy (Self-regulation Therapy for Opioid use disorder and Chronic Pain–STOP) to telehealth. We completed a mixed-method data analysis to assess the differences between the telehealth and in-person administrations. Though the telehealth group showed higher retention, the in-person group reached more diverse samples. Participants who completed the telehealth group had higher education and income, longer periods of stability on medication for opioid use disorder (MOUD) and were more likely to be White compared to participants who completed the in-person group. Individuals from minoritized and underserved groups who lack access to in-person services may fall through the gaps of healthcare in the shift to telehealth. There is a clear need for additional research on how to best support those who lack access to current comorbid chronic pain and OUD treatment modalities. ClinicalTrials.gov record number:17–1849, registered November 2017.